How would I go about proving: For a,b in Z mod n, If gcd(a,n)=1 and gcd(b,n)=1 then gcd(ab,n) = 1.
I'm not sure if this is correct because I never used the fact that a and b are in Z mod n, just that they are in Z, but I gave it a shot:
[informal]
gcd(a,n) = a(x) + n(y), some x,y in Z mod n
gcd(b,n) = b(x') + n(y'), some x',y' in Z mod n
gcd(a,n)*gcd(b,n) = 1*1 = 1 = (ax + ny)(bx' + ny')
1 = abxx' + + axny' + nybx' + nnyy' = ab(xx') + n(axy'+ybx'+nyy')
So now I have: 1 = ab(c) + n(k), for the above c,k
Does this justify me saying that gcd(ab,n) = ab(c) + n(k) = 1?
-Daon
I'm not sure if this is correct because I never used the fact that a and b are in Z mod n, just that they are in Z, but I gave it a shot:
[informal]
gcd(a,n) = a(x) + n(y), some x,y in Z mod n
gcd(b,n) = b(x') + n(y'), some x',y' in Z mod n
gcd(a,n)*gcd(b,n) = 1*1 = 1 = (ax + ny)(bx' + ny')
1 = abxx' + + axny' + nybx' + nnyy' = ab(xx') + n(axy'+ybx'+nyy')
So now I have: 1 = ab(c) + n(k), for the above c,k
Does this justify me saying that gcd(ab,n) = ab(c) + n(k) = 1?
-Daon